Analisa pengaruh social media marketing activity terhadap brand loyalty dengan mediasi brand awareness, brand trust, dan brand love - Purwianti, Lily; Fionna, Fionna (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
The study was conducted with the aim to evaluate the effect of social media marketing activity on brand loyalty mediated by brand awareness, brand trust, and brand love. Data were collected through questionnaires given to 260 respondents who live in Batam City, and are fans or users of several fast fashion brands in Indonesia, including zara, stradivarius, h&m, and uniqlo. To analyze the data, the software used is Smart PLS. The results obtained through data analysis state that social media marketing activity has a positive and significant influence on brand loyalty, brand awareness, brand trust, and also brand love. Brand loyalty is positively and significantly influenced by brand awareness, brand trust, and brand love. Brand awareness, brand trust, and brand love also mediate positively and significantly in the influence of social media marketing activity on brand loyalty.